Unprecedented superstructure in the type I family of clathrates. Issue 100 (3rd December 2021) - Yox, Philip; Lebedev, Oleg I.; Donadio, Davide; Kovnir, Kirill
Abstract : Chemical bonding preferences to optimize Ba–Au, Au–As, and As–As interactions lead to a new superstructure in type I clathrate Ba8 Au16 As30, which exhibits ultralow thermal conductivity. Abstract : The first arsenic-based clathrate exhibiting superstructural ordering due to optimization of Au–As, As–As, and Ba–Au bonding is reported. Ba8 Au16 As30 crystallizes in a unique P 21 / c monoclinic clathrate structure. The synthesis, crystal and electronic structure, and transport properties are discussed.